A Student's Guide to Philosophy. - McInerny, Ralph M. (ISI guides to the major disciplines., 2014)
A Student's Guide to Philosophy examines these questions: Who is a philosopher? Can philosophical thought be avoided? What have philosophers written over the ages? And why should we care? In this critical essay, these and other questions are posed and answered by one of America's leading philosophers, Ralph McInerny of the University of Notre Dame. Schools of thought are examined with humor and verve, and the principal works of philosophers and scholars are recommended.